Potent immune-dependent anticancer effects of the non-cardiotoxic anthracycline aclarubicin - Giulia Cerrato; Allan Sauvat; Mahmoud Abdellatif; Guido Kroemer (OncoImmunology)
Aclarubicin (also called aclacinomycin A) is an antineoplastic from the anthracycline class that is used in China and Japan but not in Europe nor in the USA. Aclarubicin induces much less DNA damage than the classical anthracyclines doxorubicin, daunorubicin, epirubicin, idarubicin, and the anthracene mitoxantrone, but is equally effective in inhibiting DNA-to-RNA transcription and in eliciting immunogenic stress in malignant cells. Accordingly, aclarubicin lacks the DNA damage-associated cardiotoxicity that is dose-limiting for classical anthracyclines. Conversely, aclarubicin is at least as potent as other anthracyclines in inducing immunogenic cell death (ICD), which is key for the mode of action of efficient chemotherapeutics. This combination of reduced toxicity and equivalent ICD-stimulatory activity may explain why, as compared to other anthracyclines, aclarubicin is particularly efficient against acute myeloid leukemia. As a result, we advocate for clinical studies seeking to replace the anthracyclines used in Western medicine by aclarubicin-like compounds. Such clinical studies should not only embrace hematological malignancies but should also concern solid cancers, including those in which ICD-inducing chemotherapies are followed by immunotherapies targeting the PD-1/PD-L1 interaction.